A Case of Torsion of Gravid Uterus Caused by Leiomyoma. (20th November 2011) - Deshpande, Gururaj; Kaul, Rajesh; P., Manjuladevi
Abstract : Uterine torsion during pregnancy is only sporadically reported in the literature. Here we present a case of leiomyoma causing uterine torsion in pregnancy and review the literature on etiology, diagnosis, and management. A 25-years-old primigravida with leiomyoma complicating pregnancy was admitted in our hospital with abdominal pain and uterine tenderness. She underwent emergency LSCS (lower segment cesarean section) for fetal bradycardia. Intraoperatively, the uterus was rotated 180 degrees left to right. Inadvertent incision on the posterior wall was avoided by proper delineation of anatomy. Torsion was corrected by exteriorization of leiomyoma and uterus, and lower segment cesarean was carried out safely. Prompt recognition and management of this condition is necessary for better maternal and fetal outcome.